On the philosophical relevance of the miracle argument - de Souza, Edna Alves [UNESP] (FapUNIFESP (SciELO), 2019)
In this article, we argue in favor of a sophisticated version of scientific realism, based on an analysis of what we consider to be the strategic element of its defense: the “miracle argument”. Scientific realism is the perspective applicable to our best scientific theories; that is, it applies to entities, processes, and relationships, etc., whether observable or unobservable, which are indispensable for explaining the empirical success of theories, and it applies particularly to those components of the theories that are crucial to achieving new and successful forecasts. The miracle argument is a type of abduction or inference to the best explanation, and is expressed in the famous formulation of Putnam (1975, p. 73): “[Scientific] realism is the only philosophy that doesn’t make the success of the science a miracle.” We analyze and refute two important modes of antirealist argument: pessimistic induction and vicious circularity of inference to the best explanation. We believe that we are justified in defending the basic intuition of scientific realism, supported by a strengthened version of the miracle argument, together with the attributes of predictive novelty and theoretical fecundity. From this perspective, science succeeds in explaining and predicting phenomena, including new phenomena, because its best theories (mature, non-ad hoc, empirically and instrumentally successful, providing new and fertile predictions, etc.) are (partially or approximately) true, and the unobservable entities postulated by these theories actually exist. We conclude that the miracle argument continues to be basic and strategic in the defense of scientific realism.
Sobre a relevância filosófica do argumento do milagre
Keywords: Anti-realism; Miracle argument; Predictive novelty; Scientific realism; Theoretical fecundity